Pyrrole polymer electrolyte membrane in energy storage lithium battery and preparation method and application thereof

By modifying the polymer matrix with pyrrole-based ionic liquids and combining it with UV gradient polymerization, the problems of low ionic conductivity and high interfacial impedance in semi-solid lithium batteries were solved. This achieved synergistic optimization of high conductivity, mechanical strength and interfacial stability, thereby improving the electrochemical performance and cycle life of the battery.

CN120914332AActive Publication Date: 2025-11-07XIAN THERMAL POWER RES INST CO LTD +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202511059617.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-30
Publication Date
2025-11-07
Estimated Expiration
2045-07-30

AI Technical Summary

Technical Problem

Existing polymer electrolytes for semi-solid lithium batteries suffer from bottlenecks such as low ionic conductivity and high interfacial impedance. Pyrrole-based ionic liquids and polar polymers are prone to microphase separation, leading to the breakage of ion transport channels and deterioration of electrode/electrolyte interface stability.

Method used

By modifying the polymer matrix with pyrrole-based ionic liquids, the synergistic stabilization of the "ionic liquid-polymer-electrode" triple interface is achieved through molecular design. The steric hindrance effect of pyrrole alkyl ionic liquids and the topology of the polymer network are utilized, combined with UV gradient polymerization process, to form a dynamic FSI-TFSI-coordination network.

Benefits of technology

It significantly improves room temperature ionic conductivity, mechanical strength and interfacial stability, achieves a high-voltage chemical stability window, and enhances the discharge specific capacity and cycle stability of semi-solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120914332A_ABST
    Figure CN120914332A_ABST
Patent Text Reader

Abstract

The invention discloses a pyrrole polymer electrolyte membrane in an energy storage lithium battery, and a preparation method and application thereof, and belongs to the field of polymer electrolyte. The method comprises the following steps: reacting 1-methylpyrrolidine with n-butyl bromide to prepare brominated 1-methyl-1-butyl pyrrolidine; the preparation method comprises the following steps: preparing 1-methyl-1-butyl pyrrolidine bis (fluoromethane sulfonyl) imide salt ionic liquid from brominated 1-methyl-1-butyl pyrrolidine and lithium bis (fluoromethane sulfonyl) imide; the preparation method comprises the following steps: uniformly mixing 1-methyl-1-butyl pyrrolidine bis (fluoromethane) sulfonimide salt ionic liquid, polyethylene glycol methyl ether methacrylate, acrylonitrile, bis (fluoromethane) sulfonimide lithium, divinylbenzene and benzoin diethyl ether, coating and curing to obtain the pyrrole ionic liquid polymer electrolyte membrane. The molecular configuration of the pyrrolidinyl ionic liquid is combined with the topological structure of a polymer network, so that triple optimization of ion transmission, mechanical strength and interface stability is realized.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of polymer electrolyte, in particular to a pyrrole polymer electrolyte film in an energy storage lithium battery, a preparation method and application thereof. BACKGROUND

[0002] With the increasing demand for battery safety in new energy vehicles and intelligent energy storage systems, traditional liquid electrolytes gradually cannot meet the demand due to defects such as flammability and leakage. Solid polymer electrolyte (SPE) has become a research hotspot due to its non-flammability and flexible processing characteristics. However, the existing SPE system still faces significant challenges: although polyacrylonitrile (PAN) as a representative of rigid polymer has excellent film-forming properties, its highly regular molecular chain arrangement limits the lithium ion migration channel, and the room temperature conductivity is much lower than the actual application requirement; although the copolymerization modification strategy by introducing flexible segments can improve the segment mobility, such as introducing poly(ethylene glycol) monomethyl ether acrylate (PEGMEMA), however, this way often sacrifices the mechanical properties, resulting in a significant decrease in material mechanical strength. More seriously, the physical contact interface between the polymer electrolyte and the electrode is easy to form micron-sized gaps, causing uneven distribution of lithium ions and accelerating the growth of lithium dendrites, which seriously threatens the cycle life of the battery. Although inorganic filler doping or complex structure design can alleviate the above problems to some extent, the blockage of the conduction path caused by filler agglomeration and the high process cost make it difficult to scale up these solutions.

[0003] To break through the performance bottleneck of solid electrolyte, ionic liquid (ILs) has become a key breakthrough due to its unique physicochemical properties. ILs not only have a wide electrochemical window and high thermal stability, but also have a liquid-like ion transport characteristic that can significantly improve the ionic conductivity of the electrolyte system. ILs containing fluorosulfonylimide anions can more effectively induce the formation of a stable solid-electrolyte interphase layer (SEI) at the electrode interface, effectively inhibiting dendrite growth, such as FSI - anion. However, there are inherent contradictions in the compounding of traditional ILs and polymer matrix: although imidazole ILs can enhance the interfacial compatibility, the cations thereof are easy to compete with lithium ions for migration, resulting in a low lithium ion transference number; although pyrrolidine ILs have better oxidation stability, they have poor compatibility with polar polymer matrix, and are easy to separate after long-term cycling, resulting in conductivity decay and mechanical property degradation. These contradictions make it difficult to improve the performance of ILs composite system. SUMMARY

[0004] The present application aims at the bottleneck problems of low ionic conductivity and large interface impedance existing in the existing semi-solid lithium battery polymer electrolyte, and proposes to use pyrrole ionic liquid to modify the polymer matrix to improve the performance. However, the pyrrole ionic liquid without structure regulation is prone to microphase separation with polar polymers, which leads to the breakage of ion transport channel and the deterioration of electrode / electrolyte interface stability, thereby restricting the improvement of electrochemical performance. In order to overcome this technical contradiction, the present application provides a pyrrole polymer electrolyte film in an energy storage lithium battery, a preparation method and application thereof, and realizes the synergistic stabilization of the three interfaces of “ionic liquid-polymer-electrode” through molecular design.

[0005] In order to achieve the above-mentioned purpose, the present application provides the following technical scheme: The present application provides a preparation method of a pyrrole polymer electrolyte film in an energy storage lithium battery, comprising: 1-methylpyrrolidine and n-bromobutane are reacted in an inert atmosphere to obtain 1-methyl-1-butyl pyrrolidine bromide ionic liquid; The 1-methyl-1-butyl pyrrolidine bromide ionic liquid and lithium bisfluoromethanesulfonimide are added into a first organic solvent to react, so as to obtain 1-methyl-1-butyl pyrrolidine bisfluoromethanesulfonimide salt ionic liquid; 1-methyl-1-butyl pyrrolidine bisfluoromethanesulfonimide salt ionic liquid, polyethylene glycol methyl ether methacrylate, acrylonitrile, lithium bis-trifluoromethanesulfonimide, divinylbenzene and benzoin ethyl ether are uniformly mixed to obtain a precursor solution; The precursor solution is subjected to film coating treatment, and the precursor solution is subjected to ultraviolet light curing treatment to obtain a pyrrole ionic liquid polymer electrolyte film.

[0006] The molar ratio of the 1-methylpyrrolidine and the n-bromobutane is 1:(1~3).

[0007] The 1-methylpyrrolidine and the n-bromobutane are reacted in an inert atmosphere to obtain 1-methyl-1-butyl pyrrolidine bromide ionic liquid, specifically: the 1-methylpyrrolidine and the n-bromobutane are stirred in an inert atmosphere at a temperature of 24~26 ℃ for 2~3 h to obtain a crude product of 1-methyl-1-butyl pyrrolidine bromide ionic liquid, and the crude product of 1-methyl-1-butyl pyrrolidine bromide ionic liquid is washed with a second organic solvent at a temperature of 0~5 ℃ to obtain 1-methyl-1-butyl pyrrolidine bromide ionic liquid; the second organic solvent includes ethyl acetate and anhydrous diethyl ether.

[0008] The molar ratio of the 1-methyl-1-butyl pyrrolidine bromide ionic liquid and the lithium bisfluoromethanesulfonimide is 1:(1~3).

[0009] The first organic solvent comprises one or more of anhydrous methanol, anhydrous ethanol or isopropyl alcohol.

[0010] The brominated 1-methyl-1-butyl pyrrolidine ionic liquid is reacted with lithium bisfluoromethanesulfonimide in the first organic solvent to obtain 1-methyl-1-butyl pyrrolidine bisfluoromethanesulfonimide salt ionic liquid, specifically, the brominated 1-methyl-1-butyl pyrrolidine ionic liquid is reacted with lithium bisfluoromethanesulfonimide in the first organic solvent for 2-3 hours, and then extraction is performed to obtain the crude product 1-methyl-1-butyl pyrrolidine bisfluoromethanesulfonimide salt ionic liquid, and the crude product 1-methyl-1-butyl pyrrolidine bisfluoromethanesulfonimide salt ionic liquid is washed with a third organic solvent; after washing, drying is performed in a vacuum environment at a temperature of 60-70 DEG C for 20-24 hours to obtain 1-methyl-1-butyl pyrrolidine bisfluoromethanesulfonimide salt ionic liquid; the third organic solvent is liquid ether.

[0011] The mass ratio of the 1-methyl-1-butyl pyrrolidine bisfluoromethanesulfonimide salt ionic liquid, polyethylene glycol methyl ether methacrylate, acrylonitrile, lithium bis-trifluoromethanesulfonimide, divinylbenzene and benzoin ethyl ether is (30-60) :(35-50) :(35-50) :(25-40) :(5-10) :(3-5).

[0012] The ultraviolet light curing treatment specifically comprises: the wavelength of the ultraviolet light used is 200-260 micrometers; first, the ultraviolet light in pulse mode is used for irradiation for 10-15 minutes, and then the ultraviolet light is used for continuous irradiation for 25-30 minutes.

[0013] The application further provides a pyrrole polymer electrolyte film in an energy storage lithium battery, which is prepared according to the preparation method of the pyrrole polymer electrolyte film in the energy storage lithium battery.

[0014] In the formula, FSI - is a bisfluoromethanesulfonimide anion.

[0015] The application further provides application of the pyrrole polymer electrolyte film in the energy storage lithium battery, and the pyrrole ionic liquid polymer electrolyte film is used for preparing a semi-solid lithium battery.

[0016] Compared with the prior art, the application has the following beneficial effects: The present application is based on a synergistic mechanism of "molecular steric hindrance regulation-micro interpenetration", and realizes the triple optimization of ion transmission-mechanical strength-interface stability by precisely designing the molecular configuration of pyrrolidine-based ionic liquid and the topological structure of polymer network. Compared with the traditional imidazole system, the saturated ring structure of pyrrolidine effectively blocks the migration of cations through steric hindrance effect, the hydrophobic butyl chain of ionic liquid and the polar ethylene oxide (EO) segment of PEGMEMA form an ordered ion-rich region through microphase separation, which greatly reduces the tortuosity of ion transmission; at the same time, the strong binding force between the rigid pyrrolidine ring and the cyan group of PAN inhibits the ionic liquid from seeping out at high temperature, and ensures the long-term cycle stability. Combined with the ultraviolet gradient polymerization process, the dynamically formed FSI - -TFSI - coordination network not only promotes the dissociation of lithium salt, but also self-adapts to the volume change of the electrode, and maintains the integrity of the interface contact. The method of the present application can solve the problem of "performance imbalance" of traditional composite electrolyte, and provides a solution with intrinsic safety and high efficiency conduction for high-voltage, wide-temperature-range semi-solid batteries.

[0017] The pyrrole-based ionic liquid polymer electrolyte film of the present application exhibits multi-dimensional performance breakthrough: in terms of electrochemical performance, the room temperature ionic conductivity reaches 1.38 x 10 -4 S / cm, and through molecular chain entanglement and crosslinking network regulation, the tensile strength remains 6.7 MPa, and the high-voltage chemical stability window at room temperature is 4.7 V, in terms of interface stability, the assembled lithium battery has a first discharge specific capacity of 156 mAh·g -1 at a rate of 0.2 C, which provides a new way for high-safety, long-life semi-solid batteries. BRIEF DESCRIPTION OF DRAWINGS

[0018] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following will briefly introduce the drawings needed to be used in the embodiments. It should be understood that the following drawings only show some embodiments of the present application, and therefore should not be regarded as a limitation on the scope. For those skilled in the art, other related drawings can also be obtained without creative labor on the basis of these drawings.

[0019] Figure 1 H NMR (Nuclear Magnetic Resonance Spectroscopy of Hydrogen) spectrum of the pyrrole polymer electrolyte film in the energy storage lithium battery prepared in Example 1; Figure 2 Tensile strength comparison chart of the polymer electrolyte films prepared in Example 1, Example 2 and Comparative Example 1; Figure 3A comparison chart of cyclic voltammograms of the polymer electrolyte films prepared for Example 1, Example 2, and Comparative Example 1. DETAILED DESCRIPTION

[0020] In order to make the technical problems to be solved by the present application, technical solutions and beneficial effects more clearly, the present application will be further described in detail below with examples. It should be understood that the specific examples described herein are only used to explain the present application, and are not intended to limit the present application.

[0021] In the present application, the term "and / or" describes the association relationship of the associated objects, which means that there can be three kinds of relationships, for example, A and / or B can represent the following cases: A exists alone, A and B exist together, and B exists alone. Wherein A and B can be singular or plural. The character " / " generally represents an "or" relationship between the associated objects before and after it.

[0022] In the present application, "at least one" means one or more, and "a plurality of" means two or more. "At least one of the following" or similar expressions means any combination of these items, including any combination of single item or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can represent: a, b, c, a-b (i.e. a and b), a-c, b-c, or a-b-c, wherein a, b, and c can be single or multiple.

[0023] It should be understood that in various embodiments of the present application, the size of the sequence number of the above processes does not mean the order of execution, and part or all of the steps can be executed in parallel or in sequence, and the execution order of the processes should be determined according to its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0024] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.

[0025] The weight of the related components mentioned in the specification of the embodiments of the present application can not only refer to the specific content of each component, but also represent the weight ratio relationship between each component, therefore, as long as the content of the related components in the specification of the embodiments of the present application is enlarged or reduced in proportion, it is within the scope disclosed in the specification of the embodiments of the present application. Specifically, the mass mentioned in the specification of the embodiments of the present application can be μg, mg, g, kg, and other mass units commonly known in the chemical field.

[0026] The application provides a preparation method of a pyrrole polymer electrolyte film in an energy storage lithium battery. 1-methylpyrrolidine and n-bromobutane are uniformly mixed and placed in an inert atmosphere to obtain 1-methyl-1-butyl pyrrolidine bromide ionic liquid through reaction; the 1-methyl-1-butyl pyrrolidine bromide ionic liquid and lithium bisfluoromethanesulfonimide are added into a first organic solvent to obtain 1-methyl-1-butyl pyrrolidine bisfluoromethanesulfonimide salt ionic liquid through reaction; 1-methyl-1-butyl pyrrolidine bisfluoromethanesulfonimide salt ionic liquid, polyethylene glycol methyl ether methacrylate, acrylonitrile (AN), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), divinylbenzene (DVB) and benzoin ethyl ether are uniformly mixed to obtain a precursor solution; the precursor solution is subjected to film coating treatment, and the precursor solution is subjected to ultraviolet light curing treatment to obtain a pyrrole ionic liquid polymer electrolyte film.

[0027] In some embodiments, the molar ratio of the 1-methylpyrrolidine and the n-bromobutane is 1:(1-3), and the appropriate molar ratio of the 1-methylpyrrolidine and the n-bromobutane is used to reduce the occurrence of side reactions in the preparation of the 1-methyl-1-butyl pyrrolidine bromide ionic liquid.

[0028] In some embodiments, the 1-methylpyrrolidine and the n-bromobutane are placed in an inert atmosphere at a temperature of 24-26°C and stirred for 2-3h to obtain a crude product of 1-methyl-1-butyl pyrrolidine bromide ionic liquid, and the crude product of 1-methyl-1-butyl pyrrolidine bromide ionic liquid is washed with a second organic solvent at a temperature of 0-5°C to obtain the 1-methyl-1-butyl pyrrolidine bromide ionic liquid; the second organic solvent includes ethyl acetate and anhydrous diethyl ether.

[0029] In some embodiments, the molar ratio of the 1-methyl-1-butyl pyrrolidine bromide ionic liquid and the lithium bisfluoromethanesulfonimide is 1:(1-3).

[0030] In some embodiments, the first organic solvent includes anhydrous methanol, anhydrous ethanol and isopropyl alcohol.

[0031] In some embodiments, the brominated 1-methyl-1-butyl pyrrolidine ionic liquid is reacted with lithium bisfluoromethanesulfonimide in a first organic solvent for 2-3 hours, and after the reaction, extraction is performed to obtain a crude product 1-methyl-1-butyl pyrrolidine lithium bisfluoromethanesulfonimide ionic liquid, the crude product 1-methyl-1-butyl pyrrolidine lithium bisfluoromethanesulfonimide ionic liquid is washed with a third organic solvent; after washing, it is dried in a vacuum environment at a temperature of 60-70 ℃ for 20-24 hours to obtain 1-methyl-1-butyl pyrrolidine lithium bisfluoromethanesulfonimide ionic liquid, and the third organic solvent is liquid ether.

[0032] In some embodiments, the mass ratio of the 1-methyl-1-butyl pyrrolidine lithium bisfluoromethanesulfonimide ionic liquid, polyethylene glycol methyl ether methacrylate, acrylonitrile, lithium bis-trifluoromethanesulfonimide, divinylbenzene and benzoin ether is (30-60) :(35-50) :(35-50) :(25-40) :(5-10) :(3-5).

[0033] In some embodiments, when the ultraviolet light is cured, the wavelength of the ultraviolet light used is 200-260 μm; first, the ultraviolet light is irradiated in pulse mode for 10-15 minutes, and then the ultraviolet light is continuously irradiated for 25-30 minutes. This method uses gradient irradiation, first, the pulse mode is used to inhibit local overheating, and the on / off cycle of the pulse mode is 1s / 2s; then the continuous irradiation mode is used to promote the polymerization reaction.

[0034] In some embodiments, the precursor solution is cast on the surface of a first film-forming mold, platinum wires are placed at each corner of the first film-forming mold, and a second film-forming mold is placed on the platinum wires to make the precursor solution spread evenly; the length of the platinum wire is 2 cm, the diameter is 35 μm, the dislocation angle of the first film-forming mold and the second film-forming mold is 45°, and the temperature during the coating process is 22-28 ℃. The platinum wire is placed in the middle of the film-forming mold, which can ensure the thickness of the polymer electrolyte membrane and also help maintain the uniformity of the film thickness.

[0035] The pyrrole ionic liquid polymer electrolyte membrane is stored in an argon-filled glove box, the water in the glove box is <0.1 ppm, and the oxygen is <0.1 ppm, which can avoid the influence of water, oxygen and the like, so that the performance of the pyrrole ionic liquid polymer electrolyte membrane is stable, and the service life is prolonged.

[0036] The pyrrole polymer electrolyte membrane for energy storage lithium batteries prepared by the preparation method has the following structure formula:

[0037] In the formula, FSI -A difluoromethane sulfonimide anion.

[0038] The present application is based on a pyrrolidinium ionic liquid composite polymer electrolyte, which realizes the synergistic optimization of ion transmission, mechanical strength and interface stability through "steric hindrance regulation-micro region interpenetration" synergistic design. Figure 1 As shown in the figure, the ionic liquid has a 1 HNMR shows characteristic peaks consistent with the theoretical structure, confirming its successful synthesis. The rigid saturated ring structure of pyrrolidinium group forms strong interaction with the cyano group of PAN through steric hindrance effect, effectively inhibiting the aggregation of ionic liquid; the hydrophobic butyl chain of ionic liquid and the oxirane segment of PEGMEMA form ordered ion transmission channels through micro phase separation, significantly reducing the lithium ion migration resistance. The tensile strength test comparison curve shows that the electrolyte membrane has significantly better mechanical strength than the traditional polymer electrolyte system while maintaining high ionic conductivity, and the balance between elongation at break and tensile strength can effectively inhibit the interface delamination during battery cycling. Linear sweep voltammetry curve shows that the electrochemical window breaks through 4.7V, which benefits from the high oxidation stability of pyrrolidinium group and the interface passivation effect of FSI - anion, which makes it suitable for high-voltage positive electrode materials. In addition, the formation of dynamic coordination network not only promotes the dissociation of lithium salt, but also adapts to the volume change of electrode, combined with the in-situ generated LiF-rich interface layer, so that the battery still maintains excellent cycle stability under wide temperature range and fast charging conditions.

[0039] The pyrrolidinium polymer electrolyte membrane provided by the present application applied to the semi-solid lithium battery in the energy storage lithium battery can significantly improve the discharge specific capacity of the semi-solid lithium battery.

[0040] In the following examples, unless otherwise specified, each material used can be obtained through ordinary channels; the test method used is the conventional method in the art.

[0041] Example 1 1.0 g of 1-methylpyrrolidine and 1.93 g of n-bromobutane were added to a three-necked flask and stirred under a nitrogen atmosphere at a temperature of 25℃ for 2 hours to obtain a crude product, brominated 1-methyl-1-butyl pyrrolidine ionic liquid; the crude product, brominated 1-methyl-1-butyl pyrrolidine ionic liquid, was washed with ethyl acetate and anhydrous diethyl ether for 3 times respectively to obtain brominated 1-methyl-1-butyl pyrrolidine ionic liquid, denoted as [PYR14]Br; [PYR14]Br was stored in a vacuum at a temperature of 0℃ for 8 hours before use; Take 1.0 g [PYR14]Br and 2.2 g LiFSI after standing in anhydrous methanol mixed evenly stirring 2 hours for reaction, the solution after reaction is placed in a separatory funnel for extraction to obtain the crude product 1-methyl-1-butyl pyrrolidine bis fluoromethane sulfonamide salt ionic liquid, washed with liquid ether 3 times, placed in a vacuum environment at 60 ℃ and dried for 24 h to obtain 1-methyl-1-butyl pyrrolidine bis fluoromethane sulfonamide salt ionic liquid, recorded as [PYR14][FSI]; Put 1.2 g [PYR14][FSI], 0.8 g PEGMEMA, 0.8 g AN, 0.6 g LiTFSI, 0.14 g DVB, 0.06 g benzoin ether into a beaker, and stir to obtain a precursor solution.

[0042] Pour the precursor solution on the surface of the first glass mold, place a platinum wire with a length of 3 cm and a diameter of 35 μm at each corner of the first glass mold; then cover the second glass mold on the platinum wire layer, and the misalignment angle of the first glass mold and the second glass mold is 45°, so that the precursor solution is evenly spread between the glass molds to the desired thickness. The temperature during the whole coating process is 22~28 ℃. Place the glass mold loaded with the precursor solution in the previous step in the ultraviolet reaction chamber, and irradiate with ultraviolet light (Ultraviolet, UV) with a wavelength of 200 μm in pulse mode (on / off cycle is 1 s / 2 s) for 25 minutes, then continuously irradiate to initiate gradient polymerization. After curing, a pyrrole ionic liquid polymer electrolyte film is obtained, recorded as PPA2-[PYR14][FSI]1.

[0043] As shown in Figure 1 The [PYR14][FSI] prepared in this embodiment has a 1 H NMR spectrum, as can be seen from the spectrum 1 H NMR (500 MHz, D2O): 3.35-3.45 (4H, C-CH2-N), 3.21-3.24 (2H, N=CH2-C), 2.95-2.98 (3H, N-CH3), 2.09-2.14 (4H, CH2-CH2), 1.65-1.72 (2H, C-CH2-C), 1.26-1.33 (2H, C-CH2-C), 0.83-0.87 (3H, -CH3). These characteristic peaks indicate that [PYR14][FSI] is successfully prepared in this embodiment, and H in each position can be found in the nuclear magnetic spectrum, and there is no obvious impurity peak in the spectrum, and the product has high purity.

[0044] The PPA2-[PYR14][FSI]1 prepared in this example was assembled with a positive electrode (lithium iron phosphate) and a negative electrode (lithium metal sheet) into a 2025 type button cell, and performance test was conducted. The conductivity at room temperature was measured to be 2.73 × 10 -4 S / cm. To detect the application of the polymer electrolyte in a semi-solid lithium battery, it was assembled into a LiFePO4 / PPA2-[PYR14][FSI]1 / Li battery, and charge-discharge cycle test was conducted at 60°C. The first discharge specific capacity of the battery was measured to be 133 mAh·g -1 .

[0045] Example 2 1.0 g of 1-methylpyrrolidine and 1.93 g of n-butyl bromide were added to a three-necked flask, and stirring was conducted under a nitrogen atmosphere at a temperature of 25°C for 2 hours to obtain a crude product, brominated 1-methyl-1-butyl pyrrolidine ionic liquid. The crude product, brominated 1-methyl-1-butyl pyrrolidine ionic liquid, was washed with ethyl acetate and anhydrous diethyl ether for 3 times respectively to obtain brominated 1-methyl-1-butyl pyrrolidine ionic liquid, denoted as [PYR14]Br. The [PYR14]Br was stored in a vacuum at a temperature of 0°C for 8 hours before use; 1.0 g of 1-methylpyrrolidine and 1.93 g of n-butyl bromide were added to a three-necked flask, and stirring was conducted under a nitrogen atmosphere at a temperature of 25°C for 2 hours to obtain a crude product, brominated 1-methyl-1-butyl pyrrolidine ionic liquid. The crude product, brominated 1-methyl-1-butyl pyrrolidine ionic liquid, was washed with ethyl acetate and anhydrous diethyl ether for 3 times respectively to obtain brominated 1-methyl-1-butyl pyrrolidine ionic liquid, denoted as [PYR14]Br. The [PYR14]Br was stored in a vacuum at a temperature of 0°C for 8 hours before use; 0.9 g of [PYR14][FSI], 0.8 g of PEGMEMA, 0.8 g of AN, 0.6 g of LiTFSI, 0.14 g of DVB, and 0.06 g of benzene ether were added to a beaker, and stirring was conducted to obtain a precursor solution.

[0046] The precursor solution was cast on the surface of a first glass mold, and one platinum wire was placed at each corner of the first glass mold, with a length of 3 cm and a diameter of 35 μm. A second glass mold was then placed on the upper layer of the platinum wires, with a misalignment angle of 45° between the first glass mold and the second glass mold, so that the precursor solution was evenly spread between the glass molds to the desired thickness. The temperature during the entire coating process was 22-28°C. The glass mold coated with the precursor solution in the previous step was placed horizontally in the UV reaction chamber, and irradiated with UV at a wavelength of 200 μm in pulse mode (1 s / 2 s on / off cycle) for 25 min, then continuous irradiation for 25 min, to initiate gradient polymerization. After curing, a pyrrole-based ionic liquid polymer electrolyte film was obtained, denoted as PPA4-[PYR14][FSI] 1.5 .

[0047] The PPA4-[PYR14][FSI] 1.5 prepared in this example was assembled into a 2025 type button cell with a positive electrode (lithium iron phosphate) and a negative electrode (metal lithium sheet) to test its performance. The room temperature conductivity was measured to be 2.67 ×10 -4 S / cm. To test the application of the polymer electrolyte in a semi-solid lithium battery, it was assembled into a LiFePO4 / PPA4-[PYR14][FSI] 1.5 / Li battery, which was tested for charge-discharge cycling at 60 ℃. The first discharge specific capacity of the battery was measured to be 136 mAh·g -1 .

[0048] Example 3 1.0 g of 1-methylpyrrolidine and 1.93 g of n-butyl bromide were added to a three-necked flask and stirred under a nitrogen atmosphere at a temperature of 25 ℃ for 2 hours to obtain a crude product, brominated 1-methyl-1-butyl pyrrolidine ionic liquid. The crude product, brominated 1-methyl-1-butyl pyrrolidine ionic liquid, was washed with ethyl acetate and anhydrous diethyl ether for 3 times respectively to obtain brominated 1-methyl-1-butyl pyrrolidine ionic liquid, denoted as [PYR14]Br. The [PYR14]Br was stored in a vacuum at a temperature of 0 ℃ for 8 hours before use; 1.0 g of 1-methylpyrrolidine and 1.93 g of n-butyl bromide were added to a three-necked flask and stirred under a nitrogen atmosphere at a temperature of 25 ℃ for 2 hours to obtain a crude product, brominated 1-methyl-1-butyl pyrrolidine ionic liquid. The crude product, brominated 1-methyl-1-butyl pyrrolidine ionic liquid, was washed with ethyl acetate and anhydrous diethyl ether for 3 times respectively to obtain brominated 1-methyl-1-butyl pyrrolidine ionic liquid, denoted as [PYR14]Br. The [PYR14]Br was stored in a vacuum at a temperature of 0 ℃ for 8 hours before use; 0.6 g of [PYR14][FSI], 0.8 g of PEGMEMA, 0.8 g of AN, 0.6 g of LiTFSI, 0.14 g of DVB, and 0.06 g of benzene ether were added to a beaker and stirred to obtain a precursor solution.

[0049] The precursor solution was cast on the surface of the first glass mold, and a platinum wire with a length of 3 cm and a diameter of 35 μm was placed at each corner of the first glass mold. Then, the second glass mold was placed on the platinum wire, and the first glass mold and the second glass mold were misaligned at an angle of 45°, so that the precursor solution was evenly spread between the glass molds to the desired thickness. The temperature during the entire coating process was 22-28 ℃. The glass mold with the precursor solution was placed horizontally in the ultraviolet reaction chamber, and a UV with a wavelength of 200 μm was used to irradiate the glass mold in pulse mode (1 s / 2 s on / off cycle) for 25 minutes, and then continuous irradiation was performed for 25 minutes to initiate gradient polymerization. After curing, a pyrrole-based ionic liquid composite polymer electrolyte was obtained, which was denoted as PPA4-[PYR14][FSI]1.

[0050] The PPA4-[PYR14][FSI]1 prepared in this example was assembled into a 2025 type button cell with a positive electrode (lithium iron phosphate) and a negative electrode (metal lithium sheet) to test the performance. The room temperature conductivity was measured to be 1.38 ×10 -4 S / cm. To detect the application of the polymer electrolyte in the semi-solid lithium battery, the LiFePO4 / PPA4-[PYR14][FSI]1 / Li battery was tested for charge-discharge cycling at 60 ℃. The initial discharge specific capacity of the battery was measured to be 142 mAh·g -1 .

[0051] Example 4 1.0 g of 1-methylpyrrolidine and 3.22 g of n-butyl bromide were added to a three-necked flask and stirred under a nitrogen atmosphere at a temperature of 26 ℃ for 3 hours to obtain a crude product, brominated 1-methyl-1-butyl pyrrolidine ionic liquid. The crude product, brominated 1-methyl-1-butyl pyrrolidine ionic liquid, was washed with ethyl acetate and anhydrous diethyl ether at a temperature of 5 ℃ for 3 times to obtain brominated 1-methyl-1-butyl pyrrolidine ionic liquid, denoted as [PYR14]Br. The [PYR14]Br was stored in a vacuum at a temperature of 0 ℃ for 8 hours before use; 1.0 g of 1-methylpyrrolidine and 3.22 g of n-butyl bromide were added to a three-necked flask and stirred under a nitrogen atmosphere at a temperature of 26 ℃ for 3 hours to obtain a crude product, brominated 1-methyl-1-butyl pyrrolidine ionic liquid. The crude product, brominated 1-methyl-1-butyl pyrrolidine ionic liquid, was washed with ethyl acetate and anhydrous diethyl ether at a temperature of 5 ℃ for 3 times to obtain brominated 1-methyl-1-butyl pyrrolidine ionic liquid, denoted as [PYR14]Br. The [PYR14]Br was stored in a vacuum at a temperature of 0 ℃ for 8 hours before use; 0.7 g [PYR14][FSI], 0.7 g PEGMEMA, 0.7 g AN, 0.5 g LiTFSI, 0.1 g DVB, 0.1 g benzene ether were added into a beaker, and stirring was performed to obtain a precursor solution.

[0052] The precursor solution was cast on the surface of a first glass mold, one platinum wire was placed at each corner of the first glass mold, the length of the platinum wire was 3 cm, and the diameter was 35 μm; a second glass mold was then placed on the upper layer of the platinum wire, the dislocation angle between the first glass mold and the second glass mold was 45°, so that the precursor solution was evenly spread between the glass molds to the desired thickness, and the temperature during the entire coating process was 22-28 ℃; The glass mold coated with the precursor solution in the previous step was placed horizontally in a UV reaction chamber, and a UV light with a wavelength of 260 μm was used to irradiate for 10 minutes in pulse mode (1 s / 2 s for the on / off cycle), and then continuous irradiation was performed for 25 minutes to initiate gradient polymerization, and a pyrrole-based ionic liquid polymer electrolyte film was obtained after curing, which was denoted as PPA3-[PYR14][FSI]1.

[0053] The PPA3-[PYR14][FSI]1 prepared in this example was assembled into a 2025 type button cell with a positive electrode (lithium iron phosphate) and a negative electrode (metal lithium sheet) to perform performance testing, and the room temperature conductivity was measured to be 2.87 ×10 -4 S / cm. To detect the application of the polymer electrolyte in a semi-solid lithium battery, it was assembled into a LiFePO4 / PPA3-[PYR14][FSI]1 / Li battery to test the charge-discharge cycle at 60 ℃; the initial discharge specific capacity of the battery was measured to be 131 mAh·g -1 .

[0054] Example 5 1.0 g of 1-methylpyrrolidine and 4.83 g of n-butyl bromide were added into a three-necked flask, and stirring was performed under a nitrogen atmosphere at a temperature of 24 ℃ for 3 hours to obtain a crude product, brominated 1-methyl-1-butyl pyrrolidine ionic liquid; the crude product, brominated 1-methyl-1-butyl pyrrolidine ionic liquid, was washed with ethyl acetate and anhydrous diethyl ether at a temperature of 3 ℃ for 3 times, respectively, to obtain brominated 1-methyl-1-butyl pyrrolidine ionic liquid, denoted as [PYR14]Br; the [PYR14]Br was stored in a vacuum at a temperature of 0 ℃ for 8 hours before use; 1.0 g [PYR14]Br and 0.85 g LiFSI after standing were added into anhydrous ethanol and stirred for 2.5 hours to react, and the solution after reaction was placed in a separatory funnel to extract to obtain a crude product 1-methyl-1-butyl pyrrolidine bisfluoromethane sulfonamide salt ionic liquid, which was washed with liquid ether for 3 times and then placed in a vacuum environment at 70 ℃ to dry for 20 h to obtain 1-methyl-1-butyl pyrrolidine bisfluoromethane sulfonamide salt ionic liquid, which was recorded as [PYR14][FSI]; 1.0 g [PYR14][FSI], 0.7 g PEGMEMA, 0.7 g AN, 0.8 g LiTFSI, 0.2 g DVB and 0.1 g benzoin ether were added into a beaker to obtain a precursor solution by stirring; The precursor solution was cast on the surface of a first glass mold, and one platinum wire was placed at each corner of the first glass mold, with a length of 3 cm and a diameter of 35 μm; then a second glass mold was placed on the upper layer of the platinum wire, and the first glass mold and the second glass mold were misaligned at an angle of 45°, so that the precursor solution was evenly spread between the glass molds to the required thickness, and the temperature during the entire coating process was 22-28 ℃; The glass mold coated with the precursor solution in the above step was placed horizontally in a UV reaction chamber, and a UV with a wavelength of 220 μm was used to irradiate in pulse mode (1 s / 2 s of on / off cycle) for 15 minutes, and then continuously irradiated for 30 minutes to initiate gradient polymerization, and a pyrrole ionic liquid polymer electrolyte membrane was obtained after curing, which was recorded as PPA 2.5 [PYR14][FSI]1.

[0055] The PPA prepared in this example 2.5 [PYR14][FSI]1 was assembled into a 2025 type button cell with a positive electrode (lithium iron phosphate) and a negative electrode (metal lithium sheet) to perform performance test, and the conductivity at room temperature was measured to be 2.52 ×10 -4 S / cm. To detect the application of the polymer electrolyte in a semi-solid lithium battery, it was assembled into a LiFePO4 / PPA 2.5 [PYR14][FSI]1 / Li battery to test the charge-discharge cycle at 60 ℃; the initial discharge specific capacity of the battery was measured to be 142 mAh·g -1

[0056] Example 6 ​1.0 g 1-methylpyrrolidine and 1.65 g n-butyl bromide were added into a three-necked flask and stirred under nitrogen atmosphere at a temperature of 25℃ for 2.5 hours to obtain a crude product of brominated 1-methyl-1-butyl pyrrolidine ionic liquid; the crude product of brominated 1-methyl-1-butyl pyrrolidine ionic liquid was washed with ethyl acetate and anhydrous diethyl ether at a temperature of 0℃ for 3 times respectively to obtain brominated 1-methyl-1-butyl pyrrolidine ionic liquid, denoted as [PYR14]Br; the [PYR14]Br was stored in vacuum at a temperature of 0℃ for 8 hours and then used; 1.0 g [PYR14]Br and 1.65 g LiFSI after standing were added into isopropyl alcohol, mixed uniformly, stirred for 3 hours for reaction, and the solution after reaction was placed in a separatory funnel for extraction to obtain a crude product of 1-methyl-1-butyl pyrrolidine bisfluoromethanesulfonimide salt ionic liquid; after washing with liquid diethyl ether for 3 times, the 1-methyl-1-butyl pyrrolidine bisfluoromethanesulfonimide salt ionic liquid was dried in vacuum at a temperature of 70℃ for 24 hours to obtain 1-methyl-1-butyl pyrrolidine bisfluoromethanesulfonimide salt ionic liquid, denoted as [PYR14][FSI]; 1.0 g [PYR14][FSI], 0.9 g PEGMEMA, 0.9 g AN, 0.5 g LiTFSI, 0.12 g DVB and 0.08 g benzoin ether were added into a beaker and stirred to obtain a precursor solution.

[0057] The precursor solution was cast on the surface of a first glass mold, one platinum wire was placed at each corner of the first glass mold, the length of the platinum wire was 3 cm and the diameter was 35 μm; a second glass mold was then placed on the upper layer of the platinum wire, the dislocation angle of the first glass mold and the second glass mold was 45°, so that the precursor solution was evenly spread between the glass molds to the required thickness, and the temperature of the whole coating process was 22~28℃; The glass mold loaded with the precursor solution in the above step was placed horizontally in a UV reaction chamber, and a UV with a wavelength of 250 μm was used to irradiate in pulse mode (the opening / closing cycle was 1 s / 2 s) for 12 minutes, and then continuously irradiated for 28 minutes to initiate gradient polymerization, and a pyrrole ionic liquid polymer electrolyte membrane was obtained after curing, denoted as PPA 2.5 [PYR14][FSI]1.

[0058] The PPA prepared in this embodiment 2.5 [PYR14][FSI]1 was assembled into a 2025 type button cell with a positive electrode (lithium iron phosphate) and a negative electrode (metal lithium sheet) to perform performance test, and the conductivity at room temperature was measured to be 2.70×10 -4 S / cm. To detect the application of the polymer electrolyte in a semi-solid lithium battery, it was assembled into a LiFePO4 / PPA 2.5-[PYR14][FSI]1 / Li battery was tested for charge-discharge cycling at 60 ℃; the first discharge specific capacity of the battery was measured to be 135 mAh·g at 0.5 C rate -1 .

[0059] Example 7 1.0 g of 1-methylpyrrolidine and 4.15 g of n-bromobutane were added to a three-necked flask and stirred under a nitrogen atmosphere at a temperature of 26 ℃ for 2 hours to obtain a crude product, brominated 1-methyl-1-butylpyrrolidinium ionic liquid; the crude product, brominated 1-methyl-1-butylpyrrolidinium ionic liquid, was washed with ethyl acetate and anhydrous diethyl ether at a temperature of 0 ℃ for 3 times, respectively, to obtain brominated 1-methyl-1-butylpyrrolidinium ionic liquid, denoted as [PYR14]Br; the [PYR14]Br was stored in a vacuum at a temperature of 0 ℃ for 8 hours and then used; 1.0 g of [PYR14]Br and 2.55 g of LiFSI after standing were added to a mixture of anhydrous methanol and isopropyl alcohol, mixed uniformly and stirred for 3 hours for reaction, and the solution after reaction was placed in a separatory funnel for extraction to obtain a crude product, 1-methyl-1-butylpyrrolidine bisfluoromethanesulfonimide salt ionic liquid, which was washed with liquid diethyl ether for 3 times and then dried in a vacuum environment at 60 ℃ for 20 h to obtain 1-methyl-1-butylpyrrolidine bisfluoromethanesulfonimide salt ionic liquid, denoted as [PYR14][FSI]; 1.0 g of [PYR14][FSI], 1.0 g of PEGMEMA, 1.0 g of AN, 0.8 g of LiTFSI, 0.12 g of DVB and 0.08 g of benzene ether were added to a beaker, and stirred to obtain a precursor solution.

[0060] The precursor solution was cast on the surface of a first glass mold, and one platinum wire was placed at each corner of the first glass mold, with a length of 3 cm and a diameter of 35 μm; a second glass mold was then placed on the upper layer of the platinum wire, and the first glass mold and the second glass mold were misaligned at an angle of 45°, so that the precursor solution was evenly spread between the glass molds to the desired thickness, and the temperature during the entire coating process was 22-28 ℃; The glass mold with the precursor solution loaded in the previous step was placed horizontally in a UV reaction chamber, and irradiated with UV at a wavelength of 250 μm in pulse mode (1 s / 2 s for the on / off cycle) for 10 minutes, and then continuously irradiated for 30 minutes, to initiate gradient polymerization, and a pyrrole ionic liquid polymer electrolyte membrane was obtained after curing, denoted as PPA3-[PYR14][FSI]1.

[0061] The PPA3-[PYR14][FSI]1 prepared in this example was assembled with a positive electrode (lithium iron phosphate) and a negative electrode (lithium metal sheet) into a 2025 type button cell, and the performance was tested. The conductivity at room temperature was measured to be 2.24 × 10 -4 S / cm. To detect the application of the polymer electrolyte in semi-solid lithium batteries, it was assembled into a LiFePO4 / PPA3-[PYR14][FSI]1 / Li battery and tested for charge-discharge cycling at 60°C. The first discharge specific capacity of the battery was measured to be 141 mAh·g -1 .

[0062] Comparative Example 1 The specific steps for preparing the polymer electrolyte film in Comparative Example 1 are as follows. 2.0 g of polyvinylidene difluoride (PVDF) and 0.40 g of LiTFSI were dissolved in 20 ml of N-methylpyrrolidone (NMP) solution. The resulting solution was poured onto the surface of a glass mold, and the polymer electrolyte film was obtained by drying in a vacuum environment at a temperature of 60°C for 24 hours, which is denoted as PVDF. The LiFePO4 / PVDF / Li battery was tested for charge-discharge cycling performance at 60°C. The conductivity of the polymer electrolyte film at room temperature was measured to be 1.26 × 10 -5 S / cm, and the first discharge specific capacity of the battery was measured to be 83 mAh·g -1 .

[0063] The mechanical properties (tensile strength and breaking strain) of the electrolyte films prepared in the examples and comparative examples were further measured using a universal experimental tensile machine. As shown in Table 1, the stress value of PVDF was the highest at about 8.4±0.1 MPa, while the strain value was poor, at 22.5%. After adding the ionic liquid to PPA, the tensile properties of PPA2-[PYR14][FSI]1 and PPA4-[PYR14][FSI] 1.5 were significantly improved. Among them, the tensile strength and breaking elongation of PPA2-[PYR14][FSI]1 were 1.6±0.1 MPa and 38.2%, respectively, and the tensile strength and breaking elongation of PPA4-[PYR14][FSI] 1.5 were 2.1±0.1 MPa and 72.3%, respectively. The high strain value of PPA4-[PYR14][FSI] 1.5 was due to the improved mobility of the PEGMEMA segment caused by the addition of the ionic liquid.

[0064] The electrochemical stability of the electrolyte films prepared in the examples and comparative examples at 25°C was evaluated by linear sweep voltammetry. As shown in Table 2, the onset potential of PPA3-[PYR14][FSI]1 was 4.6 V, which was higher than that of PPA2-[PYR14][FSI]1 and PPA4-[PYR14][FSI] 1.5 .Figure 3 As shown, the electrochemical window of PPA2-[PYR14][FSI]1 and PPA4-[PYR14][FSI] 1.5 The electrochemical windows of the electrolyte membranes are 4.5 V and 4.7 V, respectively, which indicates that PPA4-[PYR14][FSI] 1.5 Both lithium metal and high-voltage cathodes have electrochemical stability.

[0065] The present application is based on the "steric hindrance-microzone coordination" design strategy, through the precise matching of the molecular configuration of pyrrolidinium-based ionic liquid and the topological structure of polymer network, breaking through the performance bottleneck of traditional composite electrolyte. Compared with the conventional system, the saturated ring structure of pyrrolidinium significantly inhibits the competitive migration of cations and lithium ions (the lithium ion transference number is improved to 0.61) through the unique steric hindrance effect, and the layered ordered structure is confirmed by small angle X-ray scattering (SAXS). The hydrophobic butyl side chain and the oxirane segment of PEGMEMA form ordered hydrophilic-hydrophobic microzones through microphase separation, and construct low tortuosity ion transport channels, realizing the synergistic improvement of ionic conductivity and mechanical strength. At the same time, the strong interaction between the rigid pyrrolidine ring and the cyan group of PAN is characterized by the binding energy shift of X-ray photoelectron spectroscopy, which effectively anchors the ionic liquid and avoids the leakage of components in high-temperature cycle; Time of Flight Secondary Ion Mass Spectrometry (TOF-SIMS) in-depth analysis shows that FSI - The synergistic coordination network of anion and lithium salt not only promotes the efficient dissociation of lithium salt, but also generates a dense and stable LiF-rich layer in situ at the electrode interface, inhibits dendrite growth and reduces interface impedance. Combined with the dynamic regulation of ultraviolet gradient polymerization process, the electrolyte membrane exhibits stable interface contact and cycle performance in a wide temperature range (-40~120 ℃), and in-situ electrochemical impedance spectroscopy (EIS) shows that the impedance fluctuation is <5%, which provides an innovative solution with high safety and long life for high-voltage, fast-charging type semi-solid lithium batteries.

[0066] The endpoints and any values ​​of the ranges disclosed in this invention are not limited to the precise ranges or values; these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein. In the following, various technical solutions can, in principle, be combined with each other to obtain new technical solutions, which should also be considered as specifically disclosed herein.

[0067] The above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art can still make modifications or equivalent substitutions to the specific implementation of the present invention. Any modifications or equivalent substitutions that do not depart from the spirit and scope of the present invention are within the protection scope of the claims of the present invention pending approval.

Claims

1. A method for preparing a pyrrole polymer electrolyte film in an energy storage lithium battery, characterized by, The application relates to a pyrrole ionic liquid polymer electrolyte film and a preparation method thereof. 1-methyl-1-butyl pyrrolidine is reacted with n-bromobutane in an inert atmosphere to obtain 1-methyl-1-butyl pyrrolidine bromide ionic liquid; 1-methyl-1-butyl pyrrolidine bromide ionic liquid is reacted with lithium bisfluoromethanesulfonimide in a first organic solvent to obtain 1-methyl-1-butyl pyrrolidine bisfluoromethanesulfonimide ionic liquid; 1-methyl-1-butyl pyrrolidine bisfluoromethanesulfonimide ionic liquid, polyethylene glycol methyl ether methacrylate, acrylonitrile, lithium bis-trifluoromethanesulfonimide, divinylbenzene and benzoin ether are uniformly mixed to obtain a precursor solution; The precursor solution is subjected to film coating treatment and ultraviolet light curing treatment to obtain the pyrrole ionic liquid polymer electrolyte film.

2. The method of claim 1, wherein the method is characterized by: The molar ratio of the 1-methyl pyrrolidine and the n-bromobutane is 1: (1-3).

3. The method for preparing the pyrrole polymer electrolyte membrane in the energy storage lithium battery according to claim 1, characterized in that, The 1-methyl pyrrolidine and the n-bromobutane are stirred in an inert atmosphere at a temperature of 24-26 DEG C for 2-3 hours to obtain the crude product 1-methyl-1-butyl pyrrolidine bromide ionic liquid, and the crude product 1-methyl-1-butyl pyrrolidine bromide ionic liquid is washed with a second organic solvent at a temperature of 0-5 DEG C to obtain the 1-methyl-1-butyl pyrrolidine bromide ionic liquid. The second organic solvent comprises ethyl acetate and anhydrous ether. The molar ratio of the 1-methyl-1-butyl pyrrolidine bromide ionic liquid and the lithium bisfluoromethanesulfonimide is 1: (1-3).

4. The method of claim 1, wherein the method is characterized by: The first organic solvent comprises one or more of anhydrous methanol, anhydrous ethanol or isopropanol.

5. The method for preparing the pyrrole polymer electrolyte membrane in the energy storage lithium battery according to claim 1, characterized in that, The 1-methyl-1-butyl pyrrolidine bromide ionic liquid is reacted with the lithium bisfluoromethanesulfonimide in the first organic solvent for 2-3 hours, and the crude product 1-methyl-1-butyl pyrrolidine bisfluoromethanesulfonimide ionic liquid is obtained after extraction; the crude product 1-methyl-1-butyl pyrrolidine bisfluoromethanesulfonimide ionic liquid is washed with a third organic solvent; and the 1-methyl-1-butyl pyrrolidine bisfluoromethanesulfonimide ionic liquid is obtained after drying at a temperature of 60-70 DEG C in a vacuum environment for 20-24 hours.

6. The method for preparing the pyrrole polymer electrolyte membrane in the energy storage lithium battery according to claim 1, characterized in that, The third organic solvent is liquid ether. The mass ratio of the 1-methyl-1-butyl pyrrolidine bisfluoromethanesulfonimide ionic liquid, the polyethylene glycol methyl ether methacrylate, the acrylonitrile, the lithium bis-trifluoromethanesulfonimide, the divinylbenzene and the benzoin ether is (30-60) : (35-50) : (35-50) : (25-40) : (5-10) : (3-5). The ultraviolet light curing treatment is specifically as follows:

7. The method of claim 1, wherein the method is characterized by: The wavelength of the ultraviolet light is 200-260 micrometers.

8. The method for preparing the pyrrole polymer electrolyte membrane in the energy storage lithium battery according to claim 1, characterized in that, ​ ​ First, the UV light is irradiated in pulse mode for 10-15 minutes, and then the UV light is continuously irradiated for 25-30 minutes.

9. A polypyrrole electrolyte film in an energy storage lithium battery, characterized by, The preparation method of the pyrrole polymer electrolyte film in the energy storage lithium battery according to any one of claims 1-8 is prepared, and the structure formula of the pyrrole ionic liquid in the pyrrole ionic liquid polymer electrolyte film is as follows: wherein FSI - is a bisfluoromethanesulfonylimide anion.

10. Use of a pyrrole polymer electrolyte film in an energy storage lithium battery according to claim 9, characterized in that, The pyrrole ionic liquid polymer electrolyte film is used for preparing a semi-solid lithium battery.

Citation Information

Patent Citations

  • Pyrrolidine ionic liquid, and preparation method, electrolyte and capacitor thereof

    CN103965141A

  • All-solid polymer electrolyte, and preparation method and application of all-solid polymer electrolyte

    CN104538670A

  • Pyrrolidine ionic liquid as well as preparation method and application thereof

    CN114105907A

  • Polyion liquid electrolyte for lithium-sulfur battery as well as preparation method and application of polyion liquid electrolyte

    CN114976234A

  • Ionic liquid-based cross-linked network structure polymer electrolyte with high ionic conductivity and mechanical property and preparation method of ionic liquid-based cross-linked network structure polymer electrolyte

    CN117543073A